Implementasi Discussion-Comparison Method with Critical Analysis dan Learning Community Extended untuk Meningkatkan Aktivitas Belajar Mahasiswa - Irwandi; Mariana Ade Cahaya; Rizki Pratama (Universitas Hamzanwadi, 2024)
Low teacher ability can result in low student learning activities and also unsatisfactory learning outcomes obtained. This classroom action research aims to determine the application of the Discussion-Comparison Method with Critical Analysis based on Learning Community Extended(DCM-CA& LCE) to increase learning activities student. This research was carried out in three cycles, where each cycle consisted of The implementation of this research was carried out in 3 cycles, each cycle through stages (1) action preparation stage, including diagnostic and therapeutic stages, (2) action implementation stage, (3) monitoring stage and evaluation, as well as (4) analysis and reflection stages. The subjects of this research were students in the third semester of Mahasiswa Semester III Matakuliah Teknologi Pembelajaran Biologi 2 sks Program Studi Pendidikan Biologi FKIP Universitas Muhammadiyah Bengkulu. Research time: Odd Semester Academic Year 2023/2024 (September 2023-January 2024) with a total of 30 students. Activity data and learning outcomes were collected using the observation method via Observation Sheets. The results of the research showed that there was an increase in student learning activity from cycle I to cycle III in the Good category from 16.6% to 53.57%, an increase of 36.7%.